2019
DOI: 10.1016/j.jaip.2019.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Modifies the Response to Indoor Particulate Matter in Obese Urban Children with Asthma

Abstract: Background: Indoor fine particulate air pollution (PM2.5) is linked to asthma morbidity; however, whether vitamin D status influences individual susceptibility to airborne exposures is unclear. Objective: We aimed to determine if vitamin D modifies effects of indoor PM2.5 upon asthma symptoms in urban children. Methods: 120 children aged 5–12 years with physician-diagnosed asthma were evaluated at baseline and every 3 months for 9 months. Indoor PM2.5, serum 25-hydroxy vitamin D (25-OH D) levels and asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 58 publications
0
33
0
2
Order By: Relevance
“…Special Considerations: Vitamin D Vitamin D insufficiency, higher in black populations [111], has been associated with asthma prevalence and morbidity; however, a causal mechanism remains controversial. Multiple studies support a role for vitamin D via its anti-oxidant and immunomodulatory effects [112][113][114][115][116]. Two meta-analyses of randomized clinical trials demonstrate that vitamin D supplementation reduced the rate of asthma exacerbations requiring systemic corticosteroids in both children and adults in ethnically diverse populations [117•], [118].…”
Section: Materials Circumstances: Food Insecurity and Nutritionmentioning
confidence: 99%
“…Special Considerations: Vitamin D Vitamin D insufficiency, higher in black populations [111], has been associated with asthma prevalence and morbidity; however, a causal mechanism remains controversial. Multiple studies support a role for vitamin D via its anti-oxidant and immunomodulatory effects [112][113][114][115][116]. Two meta-analyses of randomized clinical trials demonstrate that vitamin D supplementation reduced the rate of asthma exacerbations requiring systemic corticosteroids in both children and adults in ethnically diverse populations [117•], [118].…”
Section: Materials Circumstances: Food Insecurity and Nutritionmentioning
confidence: 99%
“…As numerous studies have focused on the mechanism by which PM promotes the incidence of asthma, authors recently have demonstrated some strategies to improve the impact of PM on asthma. For instance, Bose et al have found that higher serum 25-hydroxy (25-OH) vitamin D levels could reduce the adverse respiratory response associated with indoor PM 2.5 exposures among obese urban children with asthma [82]. Moreover, fatty acid intake, specifically Omega-3 and Omega-6, can modify asthma severity and response to indoor air pollution in children [83].…”
Section: Strategies Modify Childhood Asthma Response To Pmmentioning
confidence: 99%
“…Vitamin D is also reported to help control asthma. (39) Bose et al demonstrated that a decreased level of vitamin D in obese children with asthma is associated with a higher level of symptoms following a 10 unit increase in PM 2.5 (41).…”
mentioning
confidence: 99%